AN INTELLIGENT MAXIMUM POWER POINT SOLAR TRACKING SYSTEM - Mirza, Nada Masood (Journal of Applied Engineering Science, 2019)
This paper accentuates the enhancement of electric energy produced from Photo Voltaic (PV) solar modules as a result of sun tracking. The development of the tracking system is based on finding the orientation of a solar module at which maximum power is delivered. Two approaches for monitoring “Real-time power” have been demonstrated namely Pulse Width Modulation (PWM) based circuit and varying resistive load using analog switches. The approaches are meant to obtain Voltage-Current (VI) curve of the solar panel and consequently locate the Maximum Power Point (MPP). A modified form of the Perturb & Observe (P&O) algorithm has been used for tracking. The tracking system has many advantages in relation to similar devices. It is intelligent in a way that it not only performs real-time power monitoring but also has the ability to store information and improve behavior based on previous tracking history. The effectiveness of the proposed tracking scheme has been demonstrated experimentally on a commercially available single axis solar tracking platform